تأثير درجة الإشباع على سلوك المواد وتأثيرها في ديمومة الطرق البيتونية - يونس, غسان (Latakia University Journal -Engineering Sciences Series, 2019)
يعتبر إنشاء طرق بديمومة عالية من الأمور الهامة جدا من الناحية الاقتصادية والاستثمارية المرورية. تؤثر في ديمومة الطرق والمطارات عوامل متعددة من أهمها جودة المواد المستخدمة وبالتالي ديمومتها واستمرارية مقاوماتها للعوامل الجوية وللإجهادات المرورية الميكانيكية وكذلك للاجهادات المائية /ضغط الماء المسامي/ وبالتالي ظهور التشوهات والتشققات الميكروية وانتقالها إلى تشوهات وشقوق ماكروية وخاصة بنتيجة اجتماع الإجهادات الناتجة عن الحمولات الميكانيكية المرورية والإجهادات المائية أي عن تغير في سلوك المواد الطرقية في حال وجود المياه وذلك من خلال تغير الخواص الفيزيائية – الميكانيكية. يستعرض هذا البحث سلوك المواد في الحالة المشبعة وكيف تؤثر الضغوط المائية في المسامات الموجودة في المادة في حالة الإشباع / زيادة الضغط المسامي / على سرعة إنتقال الشقوق والتشوهات من الحالة الميكروية ذات التأثير شبه المهمل إلى الحالة الماكروية وبالتالي إنهيار المادة وجعل الطريق غير قابل للاستخدام. تمت دراسة حالة الانتقال هذه من خلال تجارب مخبرية أجريت على مواد طرقية باستخدام جهاز الضغط ثلاثي المحاور في الحالتين المشبعة وغير المشبعة للمواد وبذلك كيف يمكن أن تتطور الشقوق الموجودة في المادة إلى الحالة الماكروية وبالتالي حالة الانهيار للمادة ومنعكسات ذلك في ديمومة الطرق. كما تم استعراض طرائق تسرب المياه من خلال المسامات والشقوق والفواصل الطولية والعرضية وتشكل الشقوق الماكروية والتكهفات في مناطق الوصل وأسفل البلاطات في القسم الأول من البحث. وجاءت خاتمة البحث بمجموعة من المقترحات والتوصيات تأكد على تأمين التصريف الجيد واستخدام طبقات دريناجية أسفل طبق التغطية للطريق The construction of highly durable roads is very important for economic reason and traffic purposes. Many factors affect the durability of roads and airports. The most important is the quality of used materials, its endurance to the weather factors and the mechanical traffic stress as well as the hydraulic stress. Therefore the appearance of the deformations and micro cracks leads to macro cracks. This research discusses the material behavior in the case of saturation and how the hydrostatic pressure affects the pores in the material during saturation (increasing the porosity pressure) on the moving speed of the cracks and the deformations from the micro state of the almost negligent effect to the macro state, the collapse of the material and making the road unable to be used. The study concluds the state of this movement throughout laboratory experiments that were held on road materials using the triaxal pressure device in both the saturated and the non-saturated state of the materials, thus the cracks that are in water could develop to the macro state and lead to collapse of the material and the impact of on the road durability. Moreover this paper reviews the ways of water leaks throughout the pores, the cracks the vertical and horizontal joint, and formation of micro cracks in the joint areas and under the concrete pavement in the first section of the research. Finally the research comes up with a number of suggestions and recommendations on the ways of applying good water drainage and the use of drainage layouts under the cover layouts of roads.